52.3: Exciton Management in Non‐doped Ultra‐thin Emissive Layers Based Organic Light‐Emitting Diodes. Issue 1 (June 2015) - Tan, Te; Ouyang, Shihong; Xie, Yingtao; Wang, Dongping; Zhu, Dalong; Xu, Xin; Fong, Hon Hang
Abstract : Non‐doped ultrathin emissive layer based OLED is demonstrated to be a promising novel structure to stimulate two‐color dual emission through exciton management. By using a ultra‐thin TAPC interlayer as a hole‐trapping layer, exciton redistribution is realized and dual emission are observed without using any doped layers. The mechanism of this trapping interlayer is further discussed.